WANITA BERHIJAB DI KAWASAN KAMPUS (Studi Kasus Fashion Hijab Temporer di Kalangan Mahasiswi Kampus Bina Widya Universitas Riau Kota Pekanbaru) - ", Halimar; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conductedincampus Bina Widya University of Riau Pekanbaru City. Target of this research is to know how knowledge of coed about hijab, and to know what meaning of hijab to coed, and also to know what the reason of coed use hijab transientlyincampus area BinaWidya University of RiauPekanbaru City. This Research entitle "Hijabers Women inArea Campus ( Case Study of Fahion Transient Hijab among Coed Campus Bina Widya University of RiauPekanbaru City). Topic focus of this research is the reason of coed use hijab transientlyin campus area BinaWidya University of RiauPekanbaru City. Informan of this research is woman using hijab transiently in campus area Bina Widya University of RiauPekanbaru City. Intake of sampel was conducted with technique of snowball sampling. Sampelis 6 coed people using hijab transiently. Writer use descriptive method qualitative and data analysed qualitative. Data instrumentisobservation, documentation and interview. Result of research indicate that the reason of coed use hijab transientlyin campus area Bina Widya University of Riau Pekanbaru City caused by feeling reluctant to instructor lecturer, existence of feeling reluctant to friend, going by the book and policy of majors, to avoid incidence ofquestion which can trigger emotion,and no demand of family. Besides from result of researchinfield known meaning of hijab to coed in campus area Bina Widya University of RiauPekanbaru City is hijab as a means of close hair of sunshine, hijab as obligation, as motivation, to show femininity symbol, and aslife style.Keyword: Hijabers Woman, Reason Of Coed Use Transient Hijab